2021
DOI: 10.3389/fnins.2021.598949
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Risperidone Treatment Associated With Enhanced Brain Activity in Patients Who Stutter

Abstract: Stuttering is a childhood onset fluency disorder that leads to impairment in speech. A randomized, double-blinded placebo-controlled study was conducted with 10 adult subjects to observe the effects of risperidone (a dopamine receptor 2/serotonin receptor 2 antagonist) on brain metabolism, using [18F] deoxyglucose as the marker. At baseline and after 6 weeks of taking risperidone (0.5–2.0 mg/day) or a placebo pill, participants were assigned to a solo reading aloud task for 30 min and subsequently underwent a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
3
15
0
Order By: Relevance
“…Recently, Maguire et al ( 2021 ) discussed this possible interaction between dopamine and metabolism, with astrocytes as a mediating link. It has been shown that astrocytes carry both D1 and D2 receptors, and that pharmacological blockade of the D2 receptors increases the metabolic activity of astrocytes in rats (Konopaske et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Maguire et al ( 2021 ) discussed this possible interaction between dopamine and metabolism, with astrocytes as a mediating link. It has been shown that astrocytes carry both D1 and D2 receptors, and that pharmacological blockade of the D2 receptors increases the metabolic activity of astrocytes in rats (Konopaske et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that astrocytes carry both D1 and D2 receptors, and that pharmacological blockade of the D2 receptors increases the metabolic activity of astrocytes in rats (Konopaske et al, 2013 ). The study by Maguire et al ( 2021 ), of persons who stutter, reported that the D2 antagonist risperidone resulted in increased uptake of glucose during speech, in the left striatum and in the Broca’s area. The stuttering was reduced in the risperidone-group, compared to the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this hypothesis, it was suggested that a defect in astrocytes can lead to developmental stuttering (a common speech disorder that affects the fluency of speech) (Han et al, 2019;Maguire et al, 2021). Thus, it will be imperative to further understand the role of astrocytes in circuits that are involved in control of vocal production.…”
Section: Antibody Namementioning
confidence: 96%
“… 14 The roles of these astrocytes in the onset of stuttering are not well characterized; however, recent studies have contributed to a growing body of evidence that dopamine receptor D2 blockers can impact stuttering behavior, perhaps because of increased astrocyte metabolism in the striatum. 15 These studies suggest that dopamine projection from the basal ganglia might contribute to disturbances in speech and vocalization, and the findings potentially support pharmacological means for treatment. 16 , 17 Recent evidence also implicates autoimmune reactions from group A beta-hemolytic streptococcus (GAS [MIM: 607395 ]) infections that target specific cell types within the basal ganglia as a potential cause of stuttering.…”
Section: Introductionmentioning
confidence: 82%